Pengaruh Corporate Social Responsibility dan Financial Slack terhadap Kinerja Keuangan Perusahaan - Nazwir, Pratiwi Winya; Raharja, Surya (Jurnal Maksipreneur, 2024)
This study wants to determine how Financial Slack and CSR disclosure affect the entity's financial performance. This study has a population of companies listed on the IDX and the Bloomberg website for 2015-2021 which have the complete financial report data needed for research. They are collecting data used in this study using a purposive sampling technique. The results showed that first, CSR disclosure negatively affects the company's financial performance. Secondly, financial slack positively affects the company's financial performance. CSR has a significant negative effect on financial performance. Therefore, companies must pay attention to the allocation and impact of CSR funds for companies.